The internal control mechanism in Treasury Finance at Berger Paints Bangladesh Ltd. - Chowdhury, Asfee Mahmud (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.